THE EFFECT OF CAPITAL STRUCTURE, CAPITAL INTENSITY AND COMPANY SIZE ON CORPORATE INCOME TAX IN THE PHARMACEUTICAL SUBSECTOR LISTED ON THE IDX FOR THE PERIOD 2016 – 2021 - Vina Mustika; Susan Sofyah; Silvia Silvia (Jurnal Ekonomi Trisakti, 2023)
This study aims to determine and verify the effect of capital sturcture, capital intensity and firm size in pharmaceutical company listed on Indonesia Stock Exchange in 2016 – 2021 with purposive samping technique obtain a sample of samples used in this research is panel data regression using E-Views 9.0 Variable in this study is corporate income tax for dependent variable and capital structure, capital intensity and firm size for independent variable. The result of the study indicate that capital structure has no effect on corporate income tax, capital intensity has a positive effect on on corporate income tax and firm size has a positive effect on corporate income tax. Keyword : Income Tax, DER, CIR , SIZE